IMPLEMENTASI SYSTEM DEVELOPMENT LIFE CYCLE PADA RANCANG BANGUN SISTEM PENDAFTARAN PASIEN BERBASIS WEB - Parasian D. P Silitonga; Doni El Rezen Purba (JSIK (Jurnal Sistem Informasi Kaputama), 2021)
The system development life cycle (SDLC) is a form of describing the stages of the system development process. The systems development life cycle presents a methodology or an organized process for building a system. One of the efforts made by the hospital to avoid long queues is to develop a web-based patient registration system. The design of the system in this study was carried out using use case diagrams and sequence diagrams. Based on the results of the process testing carried out on the applications produced in the study, it was found that the system built worked well, with no errors in the data processing process. Meanwhile, based on system interface testing, it was found that based on usability aspects, 26% of respondents chose very good; 59.4% chose good and 14.6% chose enough. Based on the user aspect 29% chose very good; 55.2% chose good and 15.6% chose enough. Based on the interaction aspect 20% chose very good; 50.8% chose good and 28.9% chose enough.